1997
DOI: 10.1055/s-2007-1013723
|View full text |Cite
|
Sign up to set email alerts
|

Successful Revascularisation for Unstable Angina of a Patient with Asymptomatic Bilateral Internal Carotid Occlusion, 70% Stenoses of the External Carotid Arteries, and Other Circulation Disturbances

Abstract: Nowadays, advanced surgical and anaesthesiological techniques of coronary artery bypass grafting minimize the risk of severe complications in patients with advanced arteriosclerotic cerebrovascular disease. Nevertheless, in case of highly compromised cerebrovascular status, the decision whether to undertake coronary artery bypass grafting or not requires special patient-related consideration. A severe, unstable angina made it necessary to perform coronary bypass grafting in a patient with bilateral internal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Adequate collateral supply would seem to be the most probable explanation; however, one of these patients had poor collateral flow and reduced cerebral flow confirmed postoperatively. Osswald et al 21 reported successful CABG for a patient with asymptomatic bilateral ICA occlusion without surgical treatment for the cerebral arterial supply, with relative changes in the cerebral blood supply monitored using laser-Doppler flow probes. They used pulsatile highflow extracorporeal circulation under mild hypothermia and maintained a mean pressure of 80 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate collateral supply would seem to be the most probable explanation; however, one of these patients had poor collateral flow and reduced cerebral flow confirmed postoperatively. Osswald et al 21 reported successful CABG for a patient with asymptomatic bilateral ICA occlusion without surgical treatment for the cerebral arterial supply, with relative changes in the cerebral blood supply monitored using laser-Doppler flow probes. They used pulsatile highflow extracorporeal circulation under mild hypothermia and maintained a mean pressure of 80 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is well known that the extraordinary reduction of CPP easily Kawabori 7 induces ischemic attack in the hemodynamically compromised patients 20 , cardiac surgery per se may potentially provoke ischemic stroke in patients with Type 3 ischemia due to ICA or MCA occlusion with or even without cardiopulmonary bypass. Although some anecdotal reports have concluded that CABG can be successfully performed without any cerebrovascular interventions in patients with ICA occlusion 8,9 , it is warranted to establish non-invasive methodology to predict the risk of perioperative ischemic stroke in patients with extracranial and intracranial artery diseases.…”
Section: Assessment Of Cerebral Perfusion Reservementioning
confidence: 99%
“…Based on the fact that the patients with impaired cerebral perfusion reserve due to ICA or MCA occlusion are at significantly higher risk for subsequent ischemic stroke 5 , the patient with coexisting ICA or MCA occlusion would also be prone to suffer ischemic stroke during cardiac surgery 6,7 . However, there are few systematic studies that denote optimal therapeutic strategy for patients with total occlusion of the ICA or middle cerebral artery (MCA) complicated by coronary artery disease requiring cardiac surgery 8,9 . Very recently, we have demonstrated that preoperative cerebrovascular screening and prophylactic cerebrovascular interventions significantly contribute to reduce the incidence of perioperative stroke in patients with occlusive carotid or vertebral artery diseases 1 .…”
Section: Introductionmentioning
confidence: 99%